Prediction of osteoporosis from proximal femoral cortical bone thickness and Hounsfield unit value with clinical significance - Xu, Gaoxiang; Wang, Daofeng; Zhang, Hao; Xu, Cheng; Li, Hua; Zhang, Wupeng; Li, Jiantao; Zhang, Licheng; Tang, Peifu (Frontiers in Surgery, 2023)
Background: Utilizing dual energy X-ray absorptiometry (DXA) to assess bone mineral density (BMD) was not routine in many clinical scenarios, leading to missed diagnoses of osteoporosis. The objective of this study is to obtain effective parameters from hip computer tomography (CT) to screen the patients with osteoporosis and predict their clinical outcomes. Methods: 375 patients with hip CT scans for intertrochanteric fracture were included. Among them, 56 patients possessed the data of both hip CT scans and DXA and were settled as training group. The cortical bone thickness (CTh) and Hounsfield unit (HU) values were abstracted from 31 regions of interest (ROI) of proximal femur. In the training group, the correlations between these parameters and BMD were investigated and their diagnostic efficiency of osteoporosis were assessed. Finally, 375 patients were divided into osteoporosis and non-osteoporosis groups based on the optimal cut-off values, and the clinical difference of subgroups was evaluated. Results: The CTh value of ROI 21 and HU value of ROI 14 were moderately correlated with the hip BMD [r=0.475 and 0.445 (p<0.001), respectively]. The best diagnostic effect could be obtained by defining osteoporosis as CTh value<3.19 mm in ROI 21 or HU value<424.97 HU in ROI 14, with the accuracy of 0.821 and 0.883, the sensitivity of 84% and 76% and the specificity of 71% and 87%, respectively. The clinical outcome of non-osteoporotic group was better than that in osteoporotic group regardless of the division criteria. Conclusion: The CTh and HU values of specific cortex sites in proximal femur were positively correlated with BMD of DXA at hip. Thresholds for osteoporosis based on CTh and HU values could be utilized to screen osteoporosis and predict clinical outcomes.